Biosensor Enhancement Using Grooved Micromixers: Part II, Experimental Studies - Lynn, N Scott; Bocková, Markéta; Adam, Pavel; Homola, Jiří (Analytical chemistry, 2015)
In this study we examine the experimental use of the staggered herringbone mixer (SHM) for the signal enhancement of a microfluidic surface plasmon resonance imaging (SPRi) affinity-based biosensor. We define the signal enhancement (Emix) as the ratio of the time-dependent slope of the sensor response of a SHM-based microfluidic channel and that of an unmixed channel; Emix is directly proportional to changes in the sensor sensitivity and inversely proportional to changes in the sensor limit of detection (LOD). Measurements were carried out for three SHM designs under a wide range of volumetric flow rates for two analytes: high diffusivity ssDNA and low diffusivity Escherichia coli bacteria. The experimental data collected in this study was found to exhibit a good match to that predicted by the numerical methods discussed in part I of this study. We found that Emix is dependent on the SHM groove geometry, the Péclet number Pe, and the overall microchannel length L; these dependencies are discussed in detail. For realistic experimental conditions, the enhancement that the SHM can provide is in the range of 1 < Emix < 5 (0% < improvement < 400%).
Keywords: Models, Biological; Surface Plasmon Resonance; Biosensing Techniques; biosenzitivní techniky; Microfluidic Analytical Techniques; povrchová plasmonová rezonance; DNA, Single-Stranded; jednovláknová DNA; mikrofluidní analytické techniky; Escherichia coli; biologické modely